SISTEM PENYEDIAAN BAHAN DAN PERALATAN PADA KONTRAKTOR SEBAGAI PENYEDIA JASA KONSTRUKSI DI KOTA DENPASAR - TJOK ISTRI PRAGANINGRUM; I GEDE ANGGA DIPUTERA; I MADE WAHYU ADITIA SASTRA PUTRA (Universitas Mahasaraswati K. Mataram, 2023)
The growing demand for and competition for construction services requires construction service providers to provide materials and equipment on time. This research was conducted in the city of Denpasar with contractors who have 7 sub-classifications of work. By distributing questionnaires to 16 contractors in Denpasar city companies with the benchmarks used are organizational structure, adequate systems and procedures and sound practices in carrying out tasks. This research used descriptive method and infrensia method. With the results of data analysis based on organizational structure benchmarks, adequate results were obtained, while for document recording, systems of authority and procedures, and healthy work practices, adequate results were obtained. So the existing system of a construction service contractor company located in the Denpasar City area needs to improve efficiency and effectiveness in an organizational structure that separates functional responsibilities.